Extraordinary bloom of toxin-producing phytoplankton enhanced by strong retention on the offshore Patagonian shelf - Guinder, Valeria Ana (2025)
The extensive Patagonian continental shelf in the Atlantic Ocean is renowned for its high productivity associated with nutrient-rich waters that fertilize massive phytoplankton blooms, especially along the shelf-break frontal system. Growing evidence reflects this ecosystem as a hotspot for harmful algal blooms (HABs). Whether these HABs reach coastal areas or are exported to the adjacent ocean basin by energetic edge currents remains unexplored. During two oceanographic cruises in spring 2021, a bloom of dinoflagellates of the Amphidomataceae family was sampled over the outer shelf with a 10 d interval, at stations 40 km apart. The bloom was first sampled on 16 November, with 32 ×106 cells L−1, and was still persistent on 25 November, with 14 ×106 cells L−1. The magnitude of this bloom is a global record for this group so far reported in the literature. The toxin azaspiracid-2 (AZA-2) was detected in both stages of the bloom, with values up to 2122 pg L−1. The most likely source of AZA-2 was Azadinium spinosum ribotype B. The bloom developed in vertically stable waters (60 m mixed layer depth) with elevated chlorophyll concentration. Water retention and the presence of fronts induced by horizontal stirring controlled the persistence and trajectory of the bloom in a localized area over the continental shelf, as evidenced by analysis of geostrophic surface currents, Lyapunov coefficients, and particle advection modelling. These findings underscore the importance of monitoring HABs in offshore environments and the need to understand biophysical interactions that govern bloom taxa assemblages and transport pathways.